2002
DOI: 10.1128/aem.68.4.2081-2084.2002
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphonate Utilization by the Thermophile Geobacillus caldoxylosilyticus T20

Abstract: A strain of Geobacillus caldoxylosilyticus from central heating system water could utilize a number of organophosphonates as the sole phosphorus source for growth at 60°C. During growth on glyphosate, aminomethylphosphonate release to the medium was observed, and in cell extracts, a glyphosate oxidoreductase-type activity, producing stoichiometric amounts of aminomethylphosphonate and glyoxylate from glyphosate, was detectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 27 publications
1
51
0
1
Order By: Relevance
“…Additionally, glyphosate utilization occurred only under conditions of P i deprivation. The authors of that study concluded that AMPA formed intracellularly from glyphosate is catabolized by C-P lyase and that AMPA cannot be taken up by the cells (113). Although this organism obviously oxidizes glyphosate, the origin of the P i extraction capability remains unclear.…”
Section: Glyphosate-utilizing Species and Strains Without Assignment mentioning
confidence: 99%
“…Additionally, glyphosate utilization occurred only under conditions of P i deprivation. The authors of that study concluded that AMPA formed intracellularly from glyphosate is catabolized by C-P lyase and that AMPA cannot be taken up by the cells (113). Although this organism obviously oxidizes glyphosate, the origin of the P i extraction capability remains unclear.…”
Section: Glyphosate-utilizing Species and Strains Without Assignment mentioning
confidence: 99%
“…As Gram-positive thermophiles, these organisms have considerable potential for applications in biotechnology and bioremediation (Obojska et al, 2002;Peng et al, 2003). Their roles in natural and artificial thermal biotypes as well as in temperate soil environments are also of interest (Marchant et al, 2002;McMullan et al, 2004).…”
Section: Implications For Geobacillus Taxonomymentioning
confidence: 99%
“…Depending on the strain, the temperature range for growth can extend as low as 35 u C or as high as 80 u C. But for most isolates, temperatures between about 45 and 70 u C are required (Nazina et al, 2001). These characteristics make Geobacillus bacteria (geobacilli) attractive to the biotechnology industry as sources of thermostable enzymes (de Champdoré et al, 2007; Karagüler et al, 2007), as platforms for biofuel production (Cripps et al, 2009;Taylor et al, 2009) and as potential components of bioremediation strategies (Markossian et al, 2000;Obojska et al, 2002;Perfumo et al, 2007). Obligate thermophiles, however, face a significant challenge outside the lab: they must survive on a planet with an average annual land surface temperature that has only ranged between 7 and 10 uC over the past three centuries (Rohde et al, 2013).…”
Section: Introduction: An Environmental Enigmamentioning
confidence: 99%